A Long Noncoding RNA Regulates Hepatitis C Virus Infection Through Interferon Alpha–Inducible Protein 6. Issue 3 (13th February 2019) - Liu, Xiao; Duan, Xiaoqiong; Holmes, Jacinta A.; Li, Wenting; Lee, Sae Hwan; Tu, Zeng; Zhu, Chuanlong; Salloum, Shadi; Lidofsky, Anna; Schaefer, Esperance A.; Cai, Dachuan; Li, Shilin; et al.
Abstract : Long noncoding RNAs (lncRNAs) play a critical role in the regulation of many important cellular processes. However, the mechanisms by which lncRNAs regulate viral infection and host immune responses are not well understood. We sought to explore lncRNA regulation of hepatitis C virus (HCV) infection and interferon response. We performed RNA sequencing (RNAseq) in Huh7.5.1 cells with or without interferon alpha (IFNα) treatment. Clustered regularly interspaced short palindromic repeats/Cas9 guide RNA (gRNA) was used to knock out selected genes. The promoter clones were constructed, and the activity of related interferon‐stimulated genes (ISGs) were detected by the secrete‐pair dual luminescence assay. We constructed the full‐length and four deletion mutants of an interferon‐induced lncRNA RP11‐288L9.4 (lncRNA‐IFI6) based on predicted secondary structure. Selected gene mRNAs and their proteins, together with HCV infection, in Huh7.5.1 cells and primary human hepatocytes (PHHs) were monitored by quantitative real‐time PCR (qRT‐PCR) and western blot. We obtained 7, 901 lncRNAs from RNAseq. A total of 1, 062 host‐encoded lncRNAs were significantly differentially regulated by IFNα treatment. We found that lncRNA‐IFI6 gRNA significantly inhibited HCV infection compared with negative gRNA control. The expression of the antiviral ISG IFI6 was significantly increased following lncRNA‐IFI6 gRNA editing compared with negative gRNA control in Japanese fulminant hepatitis 1 (JFH1)–infected Huh7.5.1 cells and PHHs. We observed that lncRNA‐IFI6 regulation of HCV was independent of Janus kinase‐signal transducer and activator of transcription (JAK‐STAT) signaling. lncRNA‐IFI6 negatively regulated IFI6 promoter function through histone modification. Overexpression of the truncated spatial domain or full‐length lncRNA‐IFI6 inhibited IFI6 expression and increased HCV replication. Conclusion: A lncRNA, lncRNA‐IFI6, regulates antiviral innate immunity in the JFH1 HCV infection model. lncRNA‐IFI6 regulates HCV infection independently of the JAK‐STAT pathway. lncRNA‐IFI6 exerts its regulatory function via promoter activation and histone modification of IFI6 through its spatial domain.